Pengaruh Sistem Penilaian terhadap Kinerja dengan Kompensasi dan Pelatihan Sebagai Variabel Intervening pada Karyawan PT Bank Tabungan Negara (Persero) Cabang Semarang - Jonas Niko Nugroho; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2016)
Today the human resources in a company plays an important role. The business world is now required creating high employee performance to the company can continue to grow and run stable. Companies should be able to build and improve performance in their environment. In improving the performance of employees of companies employ several ways, for example through an objective performance assessment, provision of adequate compensation, and training. Increasingly intense business competition resulted in the company faced with the challenge to maintain viability.This type of research uses explanatory research, with a sample of 45 respondents using Proportional Random Sampling technique is random sampling without regard to strata that exist in proportion to the number of employees in each function / unit. Data were collected through questionnaires. Data analysis methods used using classic assumption test, simple linear regression, multiple linear regression, coefficient of determination, t-test, f-test and path analysis testThis study concluded that the positive effect on the assessment system agaiant compensation, training and positive influence againts performance through variable compensation and training as a intevening variable. Furthermore, variable compensation and training also has positive influence againts performance variables.Suggestions can be submitted to Bank BTN Semarang branch is is need for greater synergy between the employees and the company in terms assesment system, compensation, and training so that policy given by the company to be well received by employees.